Effect of polyethylene glycol in graphene quantum dots for dye-sensitized solar cell - Manap A.; Mahalingam S.; Rabeya R.; Lau K.S.; Chia C.H.; Liew P.J. (Springer Science and Business Media Deutschland GmbH, 2025)
This study aims to explore the optical, structural, and chemical characteristics of polyethylene glycol (PEG) on graphene quantum dots (GQDs) for use in dye-sensitized solar cells (DSSCs). Although GQDs have the potential to enhance photon absorption in DSSCs, direct contact with the dye can lead to the degradation of GQD properties and reduced DSSC performance. To address this issue, PEG was applied as a passivation layer on GQDs co-sensitized with N719 dye, resulting in improved DSSC efficiency. The PEG-GQDs produced enhanced blue luminescence and good ultraviolet-to-visible light absorption with minimum structural defects confirmed by the Raman results. PEG also functions as a linker, facilitating the effective attachment of GQDs and dye. The nonpolar pro-oil groups on the GQD surface are adsorbed through coordination bond exchange (?OH functional group of the GQD), allowing for good dye permeability. The DSSC based on GQDs achieved a lower power conversion efficiency (0.93%) compared to the DSSC based on PEG-GQDs (1.27%). Graphical abstract: (Figure presented.) ? The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature 2024.